RETRACTED: Effects of Dexmedetomidine on Postoperative Delirium and Expression of IL-1β, IL-6, and TNF-α in Elderly Patients After Hip Fracture Operation - Zhang, Wenchao; Wang, Tianlong; Wang, Geng; Yang, Minghui; Zhou, Yan; Yuan, Yi (Frontiers in Pharmacology, 2020)
Objective Postoperative delirium (POD) is a common surgical complication in elderly patients. This study investigated the effects of dexmedetomidine on POD and pro-inflammatory markers in elderly patients with hip fracture. Methods This randomized, double-blind, controlled trial enrolled patients ≥65 years of age who underwent an operation for hip fracture at Beijing JiShuiTan Hospital from October 2016 to January 2017. The patients were divided into the DEX group (injected with dexmedetomidine 0.5 µg/kg/h) and the NS group (injected with normal saline). After surgery, the incidence of delirium at postoperative day 1 (T1), 2 (T2), and 3 (T3) was assessed using the Confusion Assessment Method delirium scale. Interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α blood levels were detected at T0 (before surgery), T1, and T3. Results Data from 240 patients were analyzed, with 120/group (intent-to-treat analysis). Dexmedetomidine decreased POD incidence (18.2 vs. 30.6%, P = 0.033). Compared to T0, all three pro-inflammatory markers were higher at T1 and then decreased at T3 (time interaction, all P < 0.001). IL-6 (P < 0.001) levels were lower in the DEX group at T1, and TNF-α (P = 0.003) levels were lower in the DEX group at T1 and T3, but IL-1β levels were similar between the two groups. The rate of adverse events was similar in the two groups. Conclusion Dexmedetomidine reduced the incidence of POD in elderly patients on the first day after hip fracture surgery, and reduced IL-6 and TNF-α levels over the first 3 days after surgery.